2018
DOI: 10.1007/s42113-018-0005-5
|View full text |Cite
|
Sign up to set email alerts
|

Do People Ask Good Questions?

Abstract: People ask questions in order to efficiently learn about the world. But do people ask good questions? In this work, we designed an intuitive, game-based task that allowed people to ask natural language questions to resolve their uncertainty. Question quality was measured through Bayesian ideal observer models that considered large spaces of possible game states. During free-form question generation, participants asked a creative variety of useful and goal-directed questions, yet they rarely asked the best ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 23 publications
1
53
0
Order By: Relevance
“…For example, Brown‐Schmidt, Gunlogson, and Tanenhaus (2008) found that participants naturally asked their partner questions about occluded objects in a task that required mutual knowledge about these objects for success. Indeed, actively highlighting and resolving known sources of uncertainty about a partner's private information may be one of the primary functions of questions in discourse (Hawkins, Stuhlmüller, Degen, & Goodman, 2015; Rothe, Lake, & Gureckis, 2018). Further work is needed to determine the resource‐rational trade‐offs of asking explicit questions about hidden distractors as opposed to implicitly increasing the specificity of one's referring expressions to account for them, as we found here.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Brown‐Schmidt, Gunlogson, and Tanenhaus (2008) found that participants naturally asked their partner questions about occluded objects in a task that required mutual knowledge about these objects for success. Indeed, actively highlighting and resolving known sources of uncertainty about a partner's private information may be one of the primary functions of questions in discourse (Hawkins, Stuhlmüller, Degen, & Goodman, 2015; Rothe, Lake, & Gureckis, 2018). Further work is needed to determine the resource‐rational trade‐offs of asking explicit questions about hidden distractors as opposed to implicitly increasing the specificity of one's referring expressions to account for them, as we found here.…”
Section: Discussionmentioning
confidence: 99%
“…One potential answer may be found in the strategies people use to actively explore the world. By asking questions (Coenen, Nelson, & Gureckis, 2018;Nelson, 2005;Rothe, Lake, & Gureckis, 2018;Wu, Meder, Filimon, & Nelson, 2017), directing eye-movements towards informative scenes (Cavanagh, Hunt, Afraz, & Rolfs, 2010;Najemnik & Geisler, 2005;Nelson & Cottrell, 2007), or sampling different options (Hertwig, Barron, Weber, & Erev, 2004;Hills & Hertwig, 2010), people are remarkably efficient at acquiring relevant information for making good decisions (Pirolli & Card, 1999;Todd, Hills, & Robbins, 2012). We investigate this capacity for active learning as a potential source of the gap between human and machine learning.…”
Section: The Gap Between Human and Machine Learningmentioning
confidence: 99%
“…These considerations may also shed new theoretical light on recent results by Rothe et al (2018) finding that in games like Battleship, people often fail to ask maximally informative natural language questions (although they can accurately rank the informativity of pre-generated questions). By embedding questioning in a social, communicative context (see also Shafto, Goodman, & Frank, 2012;Shafto, Goodman, & Griffiths, 2014), our framework suggests that this behavior may in fact be resource-rational under the conditions where most questioning takes place (Griffiths, Lieder, & Goodman, 2015).…”
Section: The Correspondence Between Questions and Goalsmentioning
confidence: 92%